1987
DOI: 10.1177/07399863870094003
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Familism and Acculturation: What Changes and What Doesn't?

Abstract: This investigation studied the effects of acculturation on attitudinal familism in 452 Hispanics compared to 227 white nonHispanics. Despite differences in the national origin of Hispanics, Mexican-, Central -and Cuban-Americans reported similar attitudes toward the family indicating that familism is a core characteristic in the Hispanic culture. Three basic dimensions of familism were found: Familial obligations, perceived support from the family and family as referents. The high level of perceived family sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
1,334
8
14

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,453 publications
(1,409 citation statements)
references
References 14 publications
53
1,334
8
14
Order By: Relevance
“…For example, familism has been described as a structure of the Latino family that explains interrelations regarding child rearing, god parenting, surrogate grand parenting, and elder caregiving (John, Resendiz, & De Vargas, 1997;Losada et al, 2010;Mendez-Luck et al, 2016;Scharlach et al, 2006). Our findings are especially consistent with those of prior literature on family interconnectedness and identification (Almeida et al, 2009;Lugo-Steidel & Contreras, 2003;Sabogal et al, 1987) as they relate to beliefs on elder caregiving.…”
Section: Discussionsupporting
confidence: 87%
“…For example, familism has been described as a structure of the Latino family that explains interrelations regarding child rearing, god parenting, surrogate grand parenting, and elder caregiving (John, Resendiz, & De Vargas, 1997;Losada et al, 2010;Mendez-Luck et al, 2016;Scharlach et al, 2006). Our findings are especially consistent with those of prior literature on family interconnectedness and identification (Almeida et al, 2009;Lugo-Steidel & Contreras, 2003;Sabogal et al, 1987) as they relate to beliefs on elder caregiving.…”
Section: Discussionsupporting
confidence: 87%
“…The tendency to place family needs above those of its' individual members, often called familism, is a central value of Asian and Latino cultures (Sabogal et al, 1987;Yee et al, 2009).…”
Section: Family Cohesionmentioning
confidence: 99%
“…The most common argument is that familism declines with time in the U.S. or across immigrant generations, which some studies find evidence for (Almeida et al, 2009). Others have found that only some aspects of familism change with duration of U.S. stay (Sabogal et al, 1987).…”
Section: Family Cohesionmentioning
confidence: 99%
“…Female adolescents may be particularly at risk for developing depressive symptoms during adolescence as a result of conflicting gender roles prescribed by the more traditional Hispanic cultural norms and those of mainstream American culture. In Hispanic cultures, high emphasis is placed on the importance of family (see Lugo Steidel and Contreras 2003;Sabogal et al 1987), particularly for females. Hispanic females are expected to be passive, to place family needs above their own, and to promote harmony among family members, even at the expense of individual well-being (Gil and Vazquez 1997).…”
Section: Depressionmentioning
confidence: 99%